If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -29 + 3x = 5x + 23 Reorder the terms: -29 + 3x = 23 + 5x Solving -29 + 3x = 23 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -29 + 3x + -5x = 23 + 5x + -5x Combine like terms: 3x + -5x = -2x -29 + -2x = 23 + 5x + -5x Combine like terms: 5x + -5x = 0 -29 + -2x = 23 + 0 -29 + -2x = 23 Add '29' to each side of the equation. -29 + 29 + -2x = 23 + 29 Combine like terms: -29 + 29 = 0 0 + -2x = 23 + 29 -2x = 23 + 29 Combine like terms: 23 + 29 = 52 -2x = 52 Divide each side by '-2'. x = -26 Simplifying x = -26
| 6x+7=-3+3x+25 | | x-0.35x=273 | | 5x+6-10x= | | y=x^3-7x^2+4x-28 | | 41-2n=2+1n | | A^6+a=0.75 | | .16-x=21 | | (-4y-4)(-12y-14)=-604 | | 7a+-3a= | | -17=n/10 | | .16x=21 | | 7.75x+4.5x=113.50 | | 48y^2+104y=-660 | | .16x+21=d | | 12x-19=53 | | (9+w)(5w+3)=0 | | 15n=15 | | y=x/3-1;x=-6 | | 3(a+-5)=-11 | | 8(5+3)-5+1= | | -4=1/3x-2 | | 79x+149y= | | 45x+(-78x)= | | 4.5x+0=9 | | log*(3*x+2)=1+log*2*x | | 3-7a=1-5a+4 | | 16x=0.8 | | 2sinx=8/5 | | .20x+6=.75 | | 9x^2-8=x^2 | | 10=1/2x-8 | | 18=h-5g |